PENINGKATAN KEMAMPUAN BERCERITA ANAK KELOMPOK B USIA 5-6 TAHUN DENGAN MEDIA BUKU CERITA BERGAMBAR DI TK RUHUI RAHAYU SAMARINDA - Arbayah; Anisah, Noor; Sjamsir, Hasbi (Manajemen Pendidikan Program Doktor, 2023)
From the observations, it is known that Ruhui Rahayu's kindergarten children's ability to tell stories is still lacking, which causesthem to be less active in the aspect of answering correctly when asked, and retelling what has been heard. There are several things that cause children to lack the ability to tell stories, one of which is less interesting media so that children feel bored. Therefore, research was conducted by applying picture storybook media to improve children's storytelling skills. The purpose of this study was to see the activities of teachers and children and improve the storytelling skills of children aged 5-6 years, in this study researchers used the Classroom Action Research CAR research method. The subjects of this study were group B children in Ruhui Rahayu Samarinda Kindergarten totaling 13 children with 6 girls and 7 boys with the object of research on the application of picture story book media in improving the storytelling skills of children aged 5-6 years. research results